Electronic cigarettes—A review of the physiological health effects - Alyssa Zucchet; Grégory Schmaltz (FACETS, 2017)
Electronic cigarettes (ECs) are devices that are used recreationally or as smoking cessation tools, and have become increasingly popular in recent years. We conducted a review of the available literature to determine the health effects caused by the use of these devices. A heating element in the EC aerosolizes a solution of propylene glycol, glycerol, nicotine (optional), and flavouring (optional). These compounds are generally harmless on their own. However, upon heating, they produce various carcinogens and irritants. We found that concentrations of these toxicants vary significantly depending on the type of EC device, the type of EC liquid, and the smoking behaviour of the user. Exposure to these vapours can cause inflammation and oxidative damage to in vitro and in vivo cells. EC aerosol can also potentially affect organ systems and especially cardiovascular and lung function. We concluded that EC use causes acute effects on health but not as severe as those of conventional cigarettes (CCs). These devices could, therefore, be of use for smokers of CCs wishing to quit. However, as EC aerosol introduces new toxicants not found in CCs, long-term studies are needed to investigate possible chronic effects associated with EC use.